Application of partial least square in predicting e-entrepreneurial intention among business students: Evidence from Pakistan - Hira Batool; Haroon Rasheed; Muhammad Imran Malik; Saddam Hussain (Journal of Innovation and Entrepreneurship, 2015)
Statistics have shown that the market is oversupplied with young and inexperienced graduates as the number of graduates has been increasing over the years. At the same time, the youth's intention toward internet due to growing funds which assist web advancement in Pakistan has steadily increased. Hence, to solve the unemployment issue among business students, there is a potential to make this self-employment an option for graduates to start on their careers. The entrepreneurial attitude orientation (EAO) scale was used to measure the students' e-entrepreneurial attitudes with mediating role of self-efficacy between creativity and e-entrepreneurial intention. A survey approach was adopted by sending questionnaires to 2420 students of public and private universities. Results show that personal control, self-esteem, and creativity with mediating role of self-efficacy were found to have significant and positive relationships with online self-employment intention. Meanwhile, achievement was found to have no significant relationship with online self-employment intention. These findings provide important insight to promote and produce a positive image of e-entrepreneurship as a career. Furthermore, the results show that the effect creativity or innovativeness is mediated by entrepreneurial self-efficacy. The results of the study provide educators, administrators, and policy makers inside and outside universities valuable insights with respect to e-entrepreneurship education. It may serve students better by increasing its focus on entrepreneurial self-efficacy and need for achievement.
Keywords: 650; Business students; Self-efficacy; Online business; Intention; EAO